Filosofi Nilai Budaya Tradisional: Melalui Makanan yang Sedap yaitu Bolu Kemojo sebagai Ikon Khas Masyarakat Melayu Riau: Pengabdian - Mis Junia; Cassey Fiernity Claresya; Muhammad Firmansyah; Laura Gita Putri Girsang; Ayu Andira Hasibuan; Dahlia Esvika; Amalia Husna; Sarintan Zahwa; Faturrahman Ananda Nur (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Traditional foods not only fulfill biological needs but also contain cultural values ​​and local philosophy that reflect a community's identity. One of Riau's signature dishes rich in cultural significance is bolu kemojo. This study aims to examine the philosophy and cultural values ​​contained in bolu kemojo as a representation of the local wisdom of the Riau Malay community. Using a descriptive qualitative approach, data was collected through literature studies and interviews with cultural figures and culinary micro, small, and medium enterprises (MSMEs) in Riau. The results show that bolu kemojo is not just a snack, but a symbol of simplicity, mutual cooperation, and respect for tradition. This dish is commonly served at traditional events, weddings, and to welcome guests of honor. The philosophy of the kemojo flower also holds spiritual significance and symbolizes beauty in Malay life. Thus, bolu kemojo serves as a medium for preserving cultural values ​​that continue to live amidst modernization.